War for Talent in Human Resource Management: Organizational Strategies for Attracting and Retaining Top Talent - Roberthair Suripatty; Victor P. K. Lengkong; Rita N. Taroreh; Christoffel M. O. Mintardjo (Maneggio, 2026)
The intensifying global competition for skilled human capital, widely termed the "War for Talent", represents one of the most consequential strategic challenges in contemporary human resource management (HRM). This systematic literature review examines organizational strategies for attracting and retaining top talent in the digital era, synthesizing evidence from twenty peer-reviewed articles published between 2021 and 2024. The findings demonstrate that effective talent war strategies operate across three interlocking phases: attraction, development, and retention. Digital transformation has fundamentally reshaped all three phases: AI-powered recruitment and talent identification systems expand access to global talent pools; continuous digital learning platforms build inimitable competencies that strengthen retention; and HR analytics enable proactive identification of flight-risk employees before attrition materializes. Employer branding emerges as a decisive differentiator in competitive talent markets, while employee empowerment and work-life balance serve as foundational retention anchors. Sector-specific analyses across healthcare, hospitality, telecommunications, and technology reveal that while the universal logic of talent attraction and retention holds, the dominant strategies and acute pressure points differ significantly by industry. The COVID-19 pandemic accelerated digital HRM innovation and elevated employee well-being as a strategic priority. A conceptual three-phase framework integrating digital tools, human-centered policies, and predictive analytics is proposed to guide organizations in developing resilient, responsive talent management systems capable of winning the war for talent sustainably.